Fundamental rights in European contract law : a comparison of the impact of fundamental rights on contractual relationships in Germany, the Netherlands, Italy and England /: a comparison of the impact of fundamental rights on contractual relationships in Germany, the Netherlands, Italy and England. (2008) - Unknown
No abstract available